Antioxidant research in Asia in the period from 2000-2008. - R.R., Hafidh; Abdulamir, Ahmed Sahib; Abu Bakar, Fatimah; Abas, Faridah; Jahanshiri, Fatemeh; Sekawi, Zamberi (Science Publications, 2009)
Problem statement: Plant antioxidants are natural plant products that inhibit the adverse effects of the Reactive Oxygen Species (ROS) produced in plants. Thus, antioxidants enable plants to survive. Depending on this principle, human beings started using some plants' parts to cure from diseases many centuries ago, even before the discovery of microbes or disclosing the etiology of many human diseases. Shed light on the importance of diet and natural products that have proved of great health impact on human traditionally and scientifically, disclosing the central role of natural antioxidants in this matter. Moreover, this review tried to give an overview on the research has so far done in Asian countries particularly in the field of natural antioxidants during the period 2000-2008. Therefore, the aim of this review is to present a comprehensive index for the antioxidant property of herbs and plants that have been traditionally used as well as experimentally proved beneficial in these countries. Approach: We had compared Asian and other nation's diet in the popularity of the traditional medicine and the type of daily meal in respect to their antioxidants contents and valuable health promoting effects. Many literatures had been collected using online search engines and the main library of University Putra Malaysia. The gathered data had been arranged alphabetically in a table depending on the plant's scientific name, common name, the used part(s) and the family name. Results: The research had shown that there were seventy-six plants with proved antioxidant activity which had been well studied by Asian scientists in the chosen period of time. Conclusion: The antioxidant components of the natural products constitute the major source of human health promotion and maintenance. The nature is still the perfect source for health promotion and for the supplementation of safe drugs. Great attention is mandatory from all the scientists around the world to explore many underestimated plants with highly effective antioxidant activity.